BIODIESEL PRODUCTION OF WASTE COOKING OIL CATALYZED BY CAO DERIVED FROM SNAIL (ACHATINA FULICA) SHELL WASTE - Edi Kurniawan; Fitra Perdana (Journal of Chemical Process and Material Technology, 2022)
Biodiesel can be production from waste cooking oil catalyzed by base heterogeneous catalysts. One type of heterogeneous base catalyst is CaO. CaO can be produced from mollusc animal waste, one of which is snail shell waste (Achatina fulica). The main constituent of snail shell waste (Achatina fulica) is a calcium oxide compound (CaCO3) which can be decomposed into CaO at high temperatures. In this study, a temperature of  900 oC for 10 hours was used to convert CaCO3 compounds into CaO compounds. Biodiesel production using CaO catalyst on the mole ratio of oil: methanol 1: 6, 3 g weight of catalyst, the reaction temperature at 60 °C, the reaction time of 3.5 hours, and stirring speed of 250 rpm with biodiesel results obtained at 84,28%.